The Effect of Stress in the Density of States of Amorphous Carbon Films Determined by X-Ray Excited Auger Electron Spectroscopy - P. F. Barbieri; F. C. Marques (Advances in Materials Science and Engineering)
Amorphous carbon films can be prepared with a large variety of structure and have been used in a number of technological applications. Many of their properties have been determined, but very little is known concerning the effect of pressure on their properties. In this work we investigate the influence of pressure of graphite-like amorphous carbon films on the density of states (DOS) using X-ray Excited Auger Electron Spectroscopy (XAES) and the second derivate method of the XAES. The films were deposited by ion beam deposition and simultaneously bombarded with argon, which is responsible for the variation of the film stress, reaching extremely high values (4.5 GPa). Marked variations of the density of states of the pπ, pσ, sp, and s components were observed with increasing stress.